Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Green Chemistry 2018
DOI: 10.5772/intechopen.71018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Green Solvents and Catalysts at the Future of Drug Design and of Synthesis

Abstract: Green chemistry is getting extended in many researches and industry areas. Not only pharmaceutical companies but also the other chemical industries started to take a step for green chemistry due to its advantages such as decreasing of waste and cost. With this respect, we have already witnessed that pharmaceutical companies searched out for green protocol when manufactured the pharmaceuticals. Green chemistry strategies can be seen in solvents, catalysts, and the others. So, we have briefly discussed the green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Meanwhile, the physical approaches to nanoparticles synthesis incorporate abundant energy and force through energy-intensive processes that result in the high cost of the end-product and also environmental consequences. Nanobiotechnology, as derived from “green chemistry”, has huge possibilities for the development of novel and crucial end-products that benefit human health, the environment and industry [ 11 ]. It is estimated that one kg of raw silver costs approximately USD 14,000, while the synthesis of one kg of AgNPs would cost around USD 4 million [ 12 ].…”
Section: Green Synthesis Of Agnpsmentioning
confidence: 99%
“…Meanwhile, the physical approaches to nanoparticles synthesis incorporate abundant energy and force through energy-intensive processes that result in the high cost of the end-product and also environmental consequences. Nanobiotechnology, as derived from “green chemistry”, has huge possibilities for the development of novel and crucial end-products that benefit human health, the environment and industry [ 11 ]. It is estimated that one kg of raw silver costs approximately USD 14,000, while the synthesis of one kg of AgNPs would cost around USD 4 million [ 12 ].…”
Section: Green Synthesis Of Agnpsmentioning
confidence: 99%
“…Green chemistry has been developed as an alternative to the use of environmentally harmful processes and products due to the serious consequences that the world is facing and the limited available time to find effective solutions [ 1 , 2 , 3 ]. According to Menges, it is suggested that green chemistry could have saved USD 65.5 billion by the end of 2020 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green chemistry has been used for advanced technologies to minimize hazardous, unwanted waste, and environmental effects. Because of the advantages of green chemistry, such as reduced waste and cost, not only pharmaceutical companies but also other chemical industries, have begun to take steps toward it [ 15 ]. In today’s world, synthetic chemists in academia and industry are continually challenged to think of more environmentally friendly ways to generate the desired target molecules [ 16 ].…”
Section: Introductionmentioning
confidence: 99%